2011
DOI: 10.1371/journal.pone.0022011
|View full text |Cite
|
Sign up to set email alerts
|

Subdominant/Cryptic CD8 T Cell Epitopes Contribute to Resistance against Experimental Infection with a Human Protozoan Parasite

Abstract: During adaptive immune response, pathogen-specific CD8+ T cells recognize preferentially a small number of epitopes, a phenomenon known as immunodominance. Its biological implications during natural or vaccine-induced immune responses are still unclear. Earlier, we have shown that during experimental infection, the human intracellular pathogen Trypanosoma cruzi restricts the repertoire of CD8+ T cells generating strong immunodominance. We hypothesized that this phenomenon could be a mechanism used by the paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 55 publications
(64 reference statements)
2
45
0
1
Order By: Relevance
“…Frequencies, phenotypes, and functions of specific CD8 + T cells in vaccinated mice after infectious challenge with T. cruzi Protective immunity against T. cruzi infection can be achieved by genetic vaccination with the ASP-2 gene following a heterologous plasmid DNA priming-recombinant adenovirus boosting regimen (De Alencar et al, 2009;Haolla et al, 2009;Dominguez et al, 2011Dominguez et al, , 2012Rigato et al, 2011). In C57BL/6 mice, protective immunity is mediated by CD8 + T cells that are specific for the immunodominant epitope VNHRFTLV (De Alencar et al, 2009;Rigato et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequencies, phenotypes, and functions of specific CD8 + T cells in vaccinated mice after infectious challenge with T. cruzi Protective immunity against T. cruzi infection can be achieved by genetic vaccination with the ASP-2 gene following a heterologous plasmid DNA priming-recombinant adenovirus boosting regimen (De Alencar et al, 2009;Haolla et al, 2009;Dominguez et al, 2011Dominguez et al, , 2012Rigato et al, 2011). In C57BL/6 mice, protective immunity is mediated by CD8 + T cells that are specific for the immunodominant epitope VNHRFTLV (De Alencar et al, 2009;Rigato et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Within the past few years, we reported that the heterologous prime-boost strategy successfully vaccinates highly susceptible A/Sn mice against systemic infection with the human intracellular protozoan parasite Trypanosoma cruzi, the causative agent of Chagas disease (American trypanosomiasis) (De Alencar et al, 2009;Haolla et al, 2009;Dominguez et al, 2011Dominguez et al, , 2012Rigato et al, 2011). In these experiments, we used a recombinant plasmid DNA for priming and the human replication-defective recombinant adenovirus type 5 for boosting, both expressing the amastigote surface protein-2 (ASP-2) of T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…ϩ T cells could limit the generation of potentially more effective parasite-focused responses capable of complete parasite eradication (21,27,62). If immunodomination by TSKB20-and TSKB18-specific CD8 ϩ T cells inhibits development of other potentially more protective CD8 ϩ responses, one would predict that TSKB20/TSKB18 Tg mice should exhibit better long-term control of T. cruzi than their WT counterparts.…”
Section: How Critical For Control Of Infection Are Cd8mentioning
confidence: 99%
“…Development of T cell-based vaccines has focused on enhancing immunodominant T cells prior to pathogen encounter, though boosting subdominant or cryptic responses has also been suggested as an important goal for vaccines (62,64). Induction of broadly focused T cell responses might be particularly important for therapeutic vaccines that enhance control of chronically infecting pathogens for which the immunodominant response has already proven ineffective at establishing an immunological cure.…”
Section: How Critical For Control Of Infection Are Cd8mentioning
confidence: 99%
“…Enhancing immune responses to subdominant antigens can confer some degree of protection against several infections (45)(46)(47)(48)(49). Pathogens like EBV restrict host T cell responses during infection, facilitating pathogen replication and/or persistence by avoiding broader immune responses.…”
Section: (2) Three Additional Cd8mentioning
confidence: 99%